DEVELOPING CRITICAL READING SKILLS THROUGH POETRY ANALYSIS (Ustozlar uchun, 2026)
Critical reading is an essential component of language learning and academic literacy, enabling students to interpret, analyze, and evaluate texts effectively. Poetry, with its rich use of imagery, symbolism, and figurative language, provides valuable opportunities for developing higher-order thinking skills. This article explores the role of poetry analysis in enhancing critical reading abilities among English language learners. It discusses how the interpretation of themes, literary devices, and multiple meanings encourages analytical thinking, cultural awareness, and linguistic competence. Furthermore, the study highlights instructional strategies that promote active engagement with poetic texts and foster independent learning. The findings suggest that poetry analysis contributes significantly to the development of critical reading skills and supports learners’ academic and intellectual growth.